INCREASING YIELD OF SUSCEPTIBLE AND RESISTANT RICE BLAST CULTIVARS USING SILICON FERTILIZATION - NurulNahar Esa; Adam Puteh; Mazidah Mat; Roslan Ismail; Mohd Rafii Yusop (Indonesian Journal of Agricultural Science, 2020)
Rice blast is one of the most critical limiting factors for rice plant growth performance. Silicon has been shown to have positive effects in controlling several plant diseases. The study aimed to investigate the impact of silicon levels on rice yield, silicon content, and panicle blast in rice plants. The study was set up as a 2 x 5 factorial experiment with three replications and arranged in a randomized complete block design. The first factors were two rice cultivars, MARDI Siraj 297 (resistant) and MR 263 (susceptible). The second factors were five levels of calcium silicate (0 g, 4 g, 8 g, 12 g, and 16 g) applied to 40 kg soil per pot. The standard fertilizers, i.e., N, P2 O5, and K2 O, were applied four times at the recommended dosage. High virulent of Pyricularia oryzae conidia (4 x 104 conidia ml-1) was sprayed using a hand sprayer (30 ml pot-1) at the time of fully completed panicle development (65 days after planting). Observed parameters were plant growth (height and culm length), yields (spikelets per panicle, grain filling percentage, and harvest index), panicle blast severity, and silica content in leaf, stem, and panicle. The results showed that silicon application reduced panicle blast severity, leading to higher yield per plant. The increase of the rice yield was a result of a significant increae in panicle per m2 , spikelet per m2 , and percentage of filled grain. Panicle blast greatly affected the performance of spikelet number per m2 , percentage of filled grain, grain weight, and yield per plant for the susceptible cultivar. Application of calcium silicate 10 g 40 kg-1 soil per pot at panicle initiation is recommended to reduce panicle blast severity hereby improve grain yield.